Moderator role of old and new Y generation differences in the effect of perceptions of self-efficiency on decision-making strategies - Tutar, Hasan; Erdem, Ahmet Tuncay; Karademir, Ömer (Emerald, 2021)
Purpose There has been a rapid generational change in the business world in Turkey recently, and X generation managers are rapidly leaving their place to Y generation managers. In countries with relatively young populations such as Turkey, management in family businesses passes into the hands of Generation Y. This study aims to examine the moderator role of the difference between old and new generation Y in the effect of self-efficacy perceptions on decision-making strategies. Design/methodology/approach This research, which was designed according to the quantitative research method, was designed according to the cross-sectional survey model, one of the general survey models. The research data were collected from a sample of 441 family business managers determined according to the simple random sampling technique. The data were analyzed and interpreted with various statistical techniques. Data analysis was done with AMOS. 20 and International Business Machines statistical package for the social sciences 22 data analysis programs. Findings According to the analysis findings, there is a significant relationship between the participants’ self-efficacy perceptions and decision-making strategies. Research findings old and new generation Y managers have different decision strategies. The research results showed that the dominant self-efficacy perceptions of the Y generation affect their decision-making strategies. Research limitations/implications This research only examines whether the old and new generation Y perceptions have a moderator function in the relationship between the participants’ self-efficacy perceptions and decision-making strategies. The research is quantitative research limited to family businesses. The results can be compared by repeating the research with other variables and in different samples, for example, by researching in public institutions. In addition, the way of reflecting the differences in perception to the management can be subjected to deeper analysis with mixed studies. Practical implications One of the important reasons for the difference in people’s approaches to events is their personality structure. Generational differences, which have been discussed primarily in recent years, make themselves felt in working life. The new working models arising from the different perspectives of the Y generation differ from the traditional business models. Today, in traditional business models, the manager profile is usually the X generation. However, the process is moving toward gaining essential positions in the management levels of the new Y generation. They put traditional managers in a difficult situation with their impatient behavior and desire to climb the career ladder quickly. Social implications In the studies conducted on the Y generation, it is understood that they do not favor the classical management approach based on the command-command relationship. The sense of loyalty of the Y generation is low compared to other generations and their organizational commitment levels are weak. There are determinations that they attach importance to flexible working style and want to do business using digital technologies. They are highly motivated in setting vision and participating in strategic decisions in organizations. These features differ significantly from the X-generation managers who adopt the traditional management approach. Originality/value Both emotional and cognitive characteristics influence decision-making behavior. The generation gap which shows common personality structures in a certain period is an important predictor of decision-making strategy. Research results and related studies significantly affect the decision strategies of the generation gap. No research has been found comparing the old and new Y generations. In this respect, it is thought that the research will contribute to theory, practice and method.
Keywords: Decision-Making; Generation; Self-Efficacy Perception; Generation Y; Decision-Making Strategies; Organizational Behavior